Residual Properties and Axial Bearing Capacity of Steel Reinforced Recycled Aggregate Concrete Column Exposed to Elevated Temperatures - Chen, Zongping; Liang, Yuhan; Mo, Linlin; Ban, Maogen (Frontiers in Materials, 2020)
This paper presents an investigation on residual properties and axial bearing capacity of steel reinforced recycled aggregate concrete (SRRC) column exposed to elevated temperature. 48 specimens were designed for the static loading test after high temperature. The variables include replacement ratios, designed temperature, target duration ,thicknesses of concrete cover, steel ratios and stirrup spacing. From this test, the mass loss ratio and stress load-deformation curve were obtained, and the influences of various parameters on residual bearing capacity were analyzed. ABAQUS was used to calculate the temperature field of specimens to get temperature damage distribution on the cross section concrete. Based on the results from testing and finite element analysis, a method of calculating the residual bearing capacity of SRRC columns under axial compression after high temperature was presented. It is shown that the bearing capacity of specimens reduced as the heated time and exposure temperature increased while it decreased as the cover thickness and steel ratio decreased. The ductility increased with the increase of steel ratio and stirrup ratio but the opposite result appears if the temperature and coverage of concrete increased. The initial damage value increased as the temperature and fire duration increased; with the increasing of replacement ratio and the decreasing of temperature, the temperature of the cross section would increase gradually. Finally, comprehensive experimental research and numerical simulation analysis results show that the calculation results are in good agreement with the experimental results.